2014
DOI: 10.1016/j.molstruc.2014.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal porosome – The secretory portal at the nerve terminal: Its structure–function, composition, and reconstitution

Abstract: Cup-shaped secretory portals at the cell plasma membrane called porosomes mediate secretion from cells. Membrane bound secretory vesicles transiently dock and fuse at the cytosolic compartment of the porosome base to expel intravesicular contents to the outside during cell secretion. In the past decade, the structure, isolation, composition, and functional reconstitution of the neuronal porosome complex has been accomplished providing a molecular understanding of its structure-function. Neuronal porosomes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
(153 reference statements)
1
4
0
Order By: Relevance
“…[ 26 27 ] Since both control and chronic HIWN-exposed animals demonstrate the decreased size of docked synaptic vesicles compared to undocked vesicles, the fractional discharge of vesicular content via porosome-mediated kiss-and-run mechanism of synaptic vesicle fusion and neurotransmitter release at large axon terminal is interfered. [ 17 18 ] This observation is consistent with our earlier findings, demonstrating that the exposure of cats to chronic noise alters the main structural parameters of porosome complex, i.e. its diameter and depth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…[ 26 27 ] Since both control and chronic HIWN-exposed animals demonstrate the decreased size of docked synaptic vesicles compared to undocked vesicles, the fractional discharge of vesicular content via porosome-mediated kiss-and-run mechanism of synaptic vesicle fusion and neurotransmitter release at large axon terminal is interfered. [ 17 18 ] This observation is consistent with our earlier findings, demonstrating that the exposure of cats to chronic noise alters the main structural parameters of porosome complex, i.e. its diameter and depth.…”
Section: Discussionsupporting
confidence: 92%
“…The final steps in neurotransmission are the docking and fusion of synaptic vesicles at the presynaptic membrane, including the “kiss-and-run” mechanism mediated by the 15 nm cup-shaped lipoprotein porosome structures [ Figure 1 ]. [ 17 18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Despite detailed analysis, we did not observe significant changes in the fine morphology of porosome complexsecretory machinery of cell, directly related to the neurotransmission (Cho et al, 2004;Jena, 2015). Therefore, we do not exclude that fine alterations take place before synaptic vesicles dock with the synaptic membrane.…”
Section: Discussionmentioning
confidence: 65%
“…For this purpose, the images of the axon terminals were enlarged onto the computer screen and each vesicle and cristae were sequentially marked, using the brush tool. For the measurement of opening diameter and the depth of porosome complex-secretory machinery of cell (Cho et al, 2004;Jena, 2015), totally 201 synaptic profiles were observed: n = 101 in PPA-treated brain and n = 100-in PBS-treated brain. Quantitative data were analysed using the Minitab software.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Results from this study provide critical insights into the aetiology of CF disease and for potential therapies. Similarly, recent studies using mass spectrometry provide some understanding of the lipidome of the neuronal porosome complex , and the role of Hsp90 in porosome assembly and function , enabling further understanding of the porosome structure–function . Currently, for further understand porosome structure–function, the major focus of our laboratory is to determine the distribution and interaction of proteins and lipids within the porosome complex using chemical crosslinking followed by mass spectrometry, and molecular modelling.…”
Section: Discovery Of the ‘Porosome’mentioning
confidence: 99%